Editorial Comment on: Transobturator Sling Suspension for Male Urinary Incontinence Including Post-Radical Prostatectomy - Onur, Rahmi (Elsevier, 2007)
[Abstract Not Available]
Keywords: article; human; male; outcome assessment; postoperative complication; priority journal; prostatectomy; surgical technique; transobturator sling suspension; urine incontinence